Differences in coder and physician perspectives on the transition to ICD-10-CM/PCS: A survey study. Issue 3 (September 2016) - Butz, Jenna; Brick, David; Rinehart-Thompson, Laurie A.; Brodnik, Melanie; Agnew, Amanda M.; Patterson, Emily S.
Abstract: Background: We hypothesized that coders would be less likely than physicians to avoid, delay, or bypass the transition to ICD-10, and more likely to want codes to distinguish between the left and right side of the body and have only one set of codes and documentation to meet both clinical and billing objectives. Objective: Assess similarities and differences in perspectives between coders and physicians on the use of ICD-10. Methods: A cross-sectional survey study was conducted with a convenience sample of coders and physicians using an online survey. Statistical differences for six a priori hypotheses were analyzed. Thematic analyses were conducted on open-ended responses. Results: 71 coders and 56 physicians completed the survey. All six hypotheses were confirmed ( p <0.001). Few physician respondents agreed that there would be clinical care (0%) or reimbursement (7%) benefits from the transition to ICD10, and the majority (59%) believed that ICD-10 will always be a burden. A considerable number of coder respondents disagreed that physicians would be willing to learn how to correctly document in support of an ICD-10 code (41%), change how they document progress notes (41%), and change how progress notes are documented following a query from a coder (32%). A number of physician respondents anticipated increasing the use of coding and documentation strategies which could reduce the data quality. Discussion: Coders and physicians have polarized perspectives on the usefulness of ICD-10. Three strategies may improve data quality and efficiency: Computer-Assisted Coding, templates, and scribes becoming certified to do codes. Highlights: Coders and physicians have polarized perspectives on the use of ICD-10. A number of physician respondents anticipated increasing the use of coding and documentation strategies which would reduce data quality. Computer-Assisted Coding (CAC), documentation templates in electronic health records, and scribes certified in coding may improve accuracy and efficiency using ICD-10.